SISTEMA AUTOMÁTICO PARA EL MONITOREO DE SERVICIOS DE AGUA POTABLE DE LA PARROQUIA PIMOCHA DEL CANTÓN BABAHOYO. - Lopez Correa, Odalis Jessenia (2018)
The EMSABA institution is a Municipal Public Company belonging to the GAD de BABAHOYO, which has as its object the attention, study, management and solution, in all the phases and processes of the citizen's needs in the provision and supply of the following services: drinking water, alcantar illadlo sanitar io, sewage treatment and discharge, drainage rainfall, flood control and collection, management and final dispositions of solid waste. Currently the processes of the drinking water system of La Parroquia Pimocha, takes it manually bringing a number of inconveniences when processing drinking water. The poor communication infrastructure and the control of the processes regarding potable water systems of La Parroquia Pimocha, cause much discomfort to the employees and users of the institution, since usually the service is interrupted frequently, which is given by not having information in real time about what is happening in the stations of pumping, which does not allow for preventive and corrective measures needed at the right time. The system focuses on wireless communication which uses a network infrastructure based on a Wi-Fi technology with an 802.11 standard, the which is a reliable, fast standard of range in standard communications 802.11, this will allow the proper control of the on or off of the water pumps, in addition it will be possible to determine the detection of the water level existing in the pumping stations, through the use of sensors which they will give with exactitude the real data of the water level. The services offered at the level of users and employees improve with the use of the technology in the processes carried out.